2020
DOI: 10.1042/cs20201268
|View full text |Cite
|
Sign up to set email alerts
|

ACE2: from protection of liver disease to propagation of COVID-19

Abstract: Twenty years ago, the discovery of angiotensin-converting enzyme 2 (ACE2) was an important breakthrough dramatically enhancing our understanding of the renin–angiotensin system (RAS). The classical RAS is driven by its key enzyme ACE and is pivotal in the regulation of blood pressure and fluid homeostasis. More recently, it has been recognised that the protective RAS regulated by ACE2 counterbalances many of the deleterious effects of the classical RAS. Studies in murine models demonstrated that manipulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 200 publications
(315 reference statements)
1
39
0
Order By: Relevance
“…A previous study also indicated that underlying diseases such as hypertension (OR = 2.72, 95% CI: 1.60, 4.64) and diabetes (OR = 3.68, 95% CI: 2.68, 5.03) are risk factors for critical disease/mortality ( 56 ). Early publications reported a “harmful hypothesis” that SARS-CoV-2 binds to target cells via angiotensin-converting enzyme 2 (ACE2), and patients with hypertension usually have increased expression of ACE2 due to the use of renin angiotensin system inhibitors ( 57 ). Although some studies indicated that ACE inhibitors (angiotensin converting enzyme inhibitors) and ARB (angiotensin-receptor blockers) therapy was harmful in COVID-19 patients, an updated meta-analysis concluded that ACEI/ARB therapy does not contribute to increased risk of mortality or severe manifestations among COVID-19 patients ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also indicated that underlying diseases such as hypertension (OR = 2.72, 95% CI: 1.60, 4.64) and diabetes (OR = 3.68, 95% CI: 2.68, 5.03) are risk factors for critical disease/mortality ( 56 ). Early publications reported a “harmful hypothesis” that SARS-CoV-2 binds to target cells via angiotensin-converting enzyme 2 (ACE2), and patients with hypertension usually have increased expression of ACE2 due to the use of renin angiotensin system inhibitors ( 57 ). Although some studies indicated that ACE inhibitors (angiotensin converting enzyme inhibitors) and ARB (angiotensin-receptor blockers) therapy was harmful in COVID-19 patients, an updated meta-analysis concluded that ACEI/ARB therapy does not contribute to increased risk of mortality or severe manifestations among COVID-19 patients ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that Ang II is the central effector that stimulates HSCs to produce pro-fibrotic cytokines, such as TGF-β1 and CTGF, which further increases hepatic resistance to portal flow and enhanced matrix formation [ 138 •, 142 ••, 143 145 ]. However, ACE2 is also the major cellular entry receptor for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) as a cellular receptor to infect alveolar epithelial cells, causing the severe respiratory disease Coronavirus disease 2019 (COVID-19) in humans [ 146 , 147 ].…”
Section: Molecular Signaling Pathways Involve In Liver Fibrosismentioning
confidence: 99%
“…Furthermore, fermented milk, another natural ACE inhibitor, is widely consumed in Bulgaria, Greece and Turkey, all of which also have had relatively low mortality rates. These findings may be mechanistically explained by a reduced production of angiotensin II (Ang II), which can act as a proinflammatory molecule, contributing to acute lung injury and favoring more severe COVID-19 manifestations ( 71 , 72 ). In addition, the microbiota present in fermented dairy products is linked to the induction of gut-mediated pulmonary immunity, providing protection against respiratory infections and inflammation ( 73 75 ).…”
Section: Dietary Factors As Possible Modulators Of Covid-19 Severity Among Patients With Smimentioning
confidence: 99%
“…Within the renin-angiotensin system (RAS), ACE produces pro-inflammatory Ang II, which is in turn cleaved by ACE2, resulting in the formation of anti-inflammatory Ang1-7. Given this association, ACE activity can be considered proinflammatory, whereas ACE2 exerts anti-inflammatory effects by opposing ACE ( 71 , 72 ). A functional insertion/deletion (I/D) polymorphism (rs1799752) in intron 16 of the ACE gene is the most studied RAS-associated polymorphic variant and ( 118 ) has been investigated among patients with SMI ( 119 128 ).…”
Section: Ace Polymorphismsmentioning
confidence: 99%